SOME ISSUES OF THE CORPUS DELICTI OF "PARTICIPATION OR INVOLVEMENT IN A CRIMINAL SUBCULTURAL GROUP" - Babakhanyan , Arman (State and Law, 2023)
The article covers some issues of the corpus delicti of "participation or involvement in a criminal subcultural group". In particular, the author of the article touched upon the problems in the legal norm of Part 2 of Article 223.3 of the RA Criminal Code. As a result the author considering the legal positions expressed in the theory of criminal law and the experience of foreign countries proposed to declare null and void that legal norm.
Keywords: criminal subculture; criminal subcultural group; thieves' world; involvement in a criminal subcultural group; criminal society; thieves’ society; association of mafia-type; thief in law